Mengkafirkan Saudaranya Tanpa Takwil: Studi Takhrij dan Syarah Hadits - Muhammad Akhdan Ruwanda (Gunung Djati Conference Series, 2023)
The purpose of this research is to discuss the hadith about the prohibition of making infidels their brothers and sisters without takwil. This study uses a qualitative approach by applying a descriptive-analytical method. The science of hadith is a formal object, while the material object is a hadith about infidels making their brothers non-believers without takwil in the history of Bukhari No. 5683. The results of the discussion of this study indicate that the status of this hadith is of the quality of shahih li dzatihi which fulfills all the qualifications for Islamic experience. This study concluded that the hadith narrated by Bukhari No. 5638 is relevant as an advice and law for people who disbelieve their brother.